2010
DOI: 10.1177/0886260510362884
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Motivations and Experiences of Unwanted Sexual Advances Among Undergraduate Students

Abstract: Objective This study examined the relationship between drinking motivations and college students’ experiences with unwanted sexual advances. Participants Undergraduates, from a public university in the mid-Atlantic region, who reported recent (30 day) alcohol use (n=289) completed an online survey midway through the spring 2007 academic semester. Methods Experiencing an unwanted sexual advance was the outcome of interest for the present study. The independent variables included socio-demographics and a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…between substance use and unwanted sexual contact. In addition to substance use predicting unwanted sexual contact (Novik, Howard, & Boekeloo, 2011;Resnick et al, 2012), the victim could also use substances as a self-medicating or coping strategy (Kaysen, Neighbors, Martell, Fossos, & Larimer, 2006;Resnick et al, 2012;Ullman & Najdowski, 2009). Selfreported misuse of prescription opioids, for example, has been associated with self-medication for depression in a sample of patients with no substance abuse history (Grattan, Sullivan, Saunders, Campbell, & Von Korff, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…between substance use and unwanted sexual contact. In addition to substance use predicting unwanted sexual contact (Novik, Howard, & Boekeloo, 2011;Resnick et al, 2012), the victim could also use substances as a self-medicating or coping strategy (Kaysen, Neighbors, Martell, Fossos, & Larimer, 2006;Resnick et al, 2012;Ullman & Najdowski, 2009). Selfreported misuse of prescription opioids, for example, has been associated with self-medication for depression in a sample of patients with no substance abuse history (Grattan, Sullivan, Saunders, Campbell, & Von Korff, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The National Institute on Alcoholism and Alcohol Abuse (NIAAA) defines a binge as a pattern of drinking that brings blood alcohol concentration to !0.08 g%, which is approximately equivalent to consuming !5 drinks (males) or !4 drinks (females) in a 2-h period (2). Binge drinking is particularly prevalent among college-aged adults (3)(4)(5)(6) and has been linked to a variety of adverse consequences in this population (7)(8)(9), making it a significant public health concern (1).…”
Section: Introductionmentioning
confidence: 99%
“…Additional consequences of college students excessively using alcohol include sexual and physical assault, dating violence, irresponsible and unplanned sexual activity, sexual harassment, disrupted sleep patterns, health issues, interference with schoolwork, and relational problems (Martin et al, 2009). Approximately 50,000 college students per year who are sexually assaulted reported having consumed alcohol at the time of the assault (Novik, Howard, & Boekeloo, 2011). Recent data also show that 83.2% of college students reported that they had engaged in unwanted sexual intercourse after they had consumed alcohol (Novik et al, 2011).…”
Section: Emerging Adult Alcohol Problemsmentioning
confidence: 99%
“…Approximately 50,000 college students per year who are sexually assaulted reported having consumed alcohol at the time of the assault (Novik, Howard, & Boekeloo, 2011). Recent data also show that 83.2% of college students reported that they had engaged in unwanted sexual intercourse after they had consumed alcohol (Novik et al, 2011). National surveys have shown that those college students who engage in heavy episodic drinking were far more likely than non–heavy drinkers to fail to appear in class, fall behind in their schoolwork, and perform below par on exams or other academic endeavors, resulting in a lower grade point average (GPA; Singleton & Wolfson, 2009).…”
Section: Emerging Adult Alcohol Problemsmentioning
confidence: 99%